Physical, cooking and thermal properties of African rice (Oryza glaberrima) and its starch digestibility in vitro. (January 2017) - Gayin, Joseph; Abdel-Aal, El-Sayed M.; Manful, John; Bertoft, Eric; Marcone, Massimo; Ragaee, Sanaa
Abstract: Rice is a staple food worldwide. In this study, seven African rice ( Oryza glaberrima ) accessions (ARAs) were evaluated for grain quality attributes, pasting, thermal and in vitro digestion properties in comparison with two Asian rice ( Oryza sativa) varieties (ARVs) and a developed cross ( O. sativa × O. glaberrima cross). The ARAs were intermediate to high amylose rice types and their 1000-kernel weight and bulk densities were comparable to the ARVs. Volume expansion ratios of cooked kernels overlapped among rice varieties ranging from 2.5 to 4.4 and the ARAs had relatively lower cooking solids loss and harder texture compared to the ARVs which were softer and more adhesive. Flours from the ARVs formed more viscous slurries, exhibiting higher breakdown viscosities than the ARAs. Gelatinization transition temperatures and enthalpies were significantly higher for flours from ARAs than the ARVs suggesting more stable crystal structure for ARAs. This is supported by the higher energy required to liquefy the retrograded ARAs flour gels. The cooked samples of ARAs and ARVs showed close starch digestibility indices with expected glycemic index (eGI) ranging from 71 to 78. Differences observed in cooking characteristics and textural properties between ARAs and ARVs may be partially due to the ARAs' high amylose content. Highlights: Cooking quality and in-vitro digestibility of African rice samples were examined. African rice accessions have medium shape, high protein and high amylose content. Texture of cooked African rice kernels was influenced by its high amylose content. Expected glycemic indices of coked African and Asian rice kernels were different.